Pengaruh Struktur Modal dan Ukuran Perusahaan terhadap Nilai Perusahaan pada Perushaan Manufaktur Sektor Industri yang Terdaftar di Bei - Mustari, Mustari; Novianti, Novianti (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The value of the company is indirectly taken into consideration to obtain profit or again in a certain period. Information regarding thr capital structure and size of the company provides assistance to investors in avaluating the performance of a company and supports the investment decision making process. Thus, it is important to ascertain whether these two variables have an impact on company. This research aims to analyze the influence of capital structure and company size on company value. Multiple linear regression analysis with quantitave analysis is the methodological technique used. Data from 63 automotive sub-sector companies listed on the Indonesia Stock Exchange for the 2016-2022 period. The findings state that the capital structure variable has positif and significant effect on campany value, company size partially has a negative and significant effect on company value. Keywords: Capital Structure, Company Size, Company Value.